Osobennosti reaktsii sistemy krovi pri gipokineticheskom stresse i sovremennye predstableniya ob immuno-nejro-endokrinnykh vzaimodejstviyakh i "tsikle okisi azota" - Kamskova, Yu. G. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
The reduction of motor activity is connected to automation and mechanization in almost all kinds of the activity of a human now. The consequences of an inactive way of life of a human are: the hypodynamy, the chronic stress, various diseases of adaptation. According to modern representations, the changes in the system of blood typical for the stress-reaction are observed at various stages of hypokinesy. This article is devoted to the research of the mechanisms of the negative influence of the hypokinesy on an organism.